2020
DOI: 10.1074/jbc.ra120.013095
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of insulin receptor substrate-2 impairs growth but not insulin function in rats

Abstract: Insulin receptor substrate (IRS)-2, along with IRS-1, is a key signaling molecule that mediates the action of insulin and insulin-like growth factor (IGF)-I. The activated insulin and IGF-I receptors phosphorylate IRSs on tyrosine residues, leading to the activation of downstream signaling pathways and the induction of various physiological functions of insulin and IGF-I. Studies using IRS-2 knockout (KO) mice showed that the deletion of IRS-2 causes type 2 diabetes due to peripheral insulin resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In this region, both combined-population and cross-population GWAS simultaneously identified anoctamin 1 (ANO1) gene, which was also known as TMEM16A. ANO1 and IRS2 played positive roles in insulin secretion (Dong et al, 2006;Xu et al, 2014;Hashimoto et al, 2015;Toyoshima et al, 2020), which could affect growth rate and fat deposition in pigs. ANO1 gene defects or its expression in pancreatic islets might influence cytokine expression and elicit an immune response that could result in death of β cell (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this region, both combined-population and cross-population GWAS simultaneously identified anoctamin 1 (ANO1) gene, which was also known as TMEM16A. ANO1 and IRS2 played positive roles in insulin secretion (Dong et al, 2006;Xu et al, 2014;Hashimoto et al, 2015;Toyoshima et al, 2020), which could affect growth rate and fat deposition in pigs. ANO1 gene defects or its expression in pancreatic islets might influence cytokine expression and elicit an immune response that could result in death of β cell (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies in mice have reported that Irs1 is essential for body growth (11), but Irs2 contributed to normal body growth only a little (13). On the other hand, recent studies have shown that Irs2 is required for normal body growth in rats (14) and that Irs2 protein potentially plays a role in the growthpromoting mechanism with some specific interacting molecule(s) (50). Irs2 is crucial for various physiological functions, including maintaining energy homeostasis (12,51), and the Erk1/2 contributes to various cell-fate determinations such as proliferation and differentiation (52), the elucidation of the H 2 O 2 -induced Irs2b-MAPK function should be a crucial research subject.…”
Section: Importance Of Irs2b On Mapk-pathway In Re-oxygenation Conditionmentioning
confidence: 99%
“…Instead, Irs2 deficient mice show severe hepatic insulin resistance, impaired beta-cell proliferation, insulin secretion, and diabetic symptoms caused outside of growth (12,13). However, a recent knockout study has shown that deletion of the Irs2 gene in rats causes significant growth retardation (14). In addition, the role of Irs1 was examined in a catch-up growth model using zebrafish and found it was responsible for the survival of multipotent cells vital for the growth spurt (15).…”
Section: Introductionmentioning
confidence: 99%